Pengaruh Dosis Pupuk Kompos Kelinci terhadap Pertumbuhan dan Hasil Pakcoy - Rahmatika, Widyana; Habibi, Imam; Andayani, Retno Dwi; Rohmah, Dewi Afiatur (Agrosains : Jurnal Penelitian Agronomi, 2022)
The study understood the influence of giving rabbit manure ordure to nitrogen uptake, growth, and yield of pakcoy and how to judge the effect of different doses of rabbit manure on nitrogen uptake, growth, and yield of pakcoy plants. The survey was conducted in October-November 2021. The method used was a non-factorial Block Design of Randomized. The factor consisted of 6 dose levels which were repeated four times. The element was the provision of rabbit manure to pakcoy plants, composed of 6 groups of rabbit manure fertilizer doses. K0 = 0 Kg/ha, K1 = 2500 kg per hectare K2 = 5000 Kg per hectare, K3 = 7500 Kg per hectare, K4 = 10000 Kg per hectare and K5 = 12500 Kg per hectare. The results showed that all observed variables were affected: plant height, leaf number, and leaf area at the age of 27 days after planting. Each K3 variable has better growth and yields, like fresh plant weight and total N uptake. K3 treatment had the best results but was not significantly different from K2, K4, and K5.